Influence of Light, Temperature, and Macronutrients on Growth and Scopolamine Biosynthesis in Duboisia species - Ullrich, Sophie Friederike; Rothauer, Andreas; Hagels, Hansjörg; Kayser, Oliver (Planta Medica, 2017)
Scopolamine is used in the pharmaceutical industry as a precursor in the organic synthesis of different classes of important active substances and is extracted in large scale from field grown Duboisia plants. Previous research revealed that plant growth as well as production of scopolamine and its derivatives varies strongly depending on abiotic factors. However, only a small amount of systematic research has been done on the influence of environmental conditions on scopolamine and biomass production, so far. In order to extend knowledge in this field, plants of three different genotypes (wild type Duboisia myoporoides and hybrids of D. myoporoides and Duboisia leichhardtii) were grown in climate chambers under controlled conditions in order to systematically analyse the influence of temperature (20, 24, 28 °C), light (50–300 µmol/m2 × s, 12, 18, 24 h per day) and macronutrients (nitrogen, calcium, potassium) on growth and scopolamine biosynthesis. The data indicate that light intensity and daily exposure to light have a major impact on scopolamine production and plant development, whereas temperature only shows a minor influence. Nitrogen (N) positively affects biomass production with increasing levels up to 4 mM, but is negatively correlated with scopolamine content. Calcium (Ca) shows a negative influence on scopolamine biosynthesis at increased levels above 1 mM as well. Potassium (K) neither affects biomass nor scopolamine production within the tested concentration range (0.05–4 mM). All in all, it can be concluded that light intensity and nitrogen supply are especially important regulating variables that can be applied in a targeted manner for influencing scopolamine and biomass production.
Keywords: Solanaceae; Duboisia; light; temperature; macronutrients; scopolamine; biosynthesis